Metodologia del manejo de informacion agroclimitica aplicada a frijol - Jones, Peter G. (International Center for Tropical Agriculture, 1979)
A detailed presentation is made of the methodology to be used in order to handle agroclimatic information correctly when applied to bean cultivation in L.A. The 2 steps involve (1) the definition of bean-cultivating areas (microregions) and (2) the compilation, accumulation, recovery and interpretation of meteorological, agronomic and edaphic data. (CIAT)